Quasi in domo propria sub securitate sanaretur: a peace agreement between King Swein Forkbeard and Duke Richard II of Normandy. - Bauduin, Pierre (Early Medieval Europe, 2021)
In his Gesta Normannorum Ducum, William of Jumièges related that the Danish king Swein Forkbeard, at the outset of his conquest of England, came to Rouen and met Richard II. Both leaders negotiated a peace agreement that authorized the Danes to sell their booty in Normandy and provided them with assistance and security. This article examines the circumstances and the clauses of the agreement and its place in the narrative of the Gesta. The author linked the circumstances of the agreement to the St Brice's Day massacre, which provided him with the opportunity to present a very negative portrait of King Æthelred II. While one should be very careful about the author's claims and chronology, a comparison with other similar agreements renders the terms of the treaty, as related by William, plausible.